Hydrothermal synthesis of NiFe2O4 nanoparticles as an efficient electrocatalyst for the electrochemical detection of bisphenol A. (30th April 2020) - Kesavan, Ganesh; Nataraj, Nandini; Chen, Shen-Ming; Lin, Li-Heng
Abstract : In this study, the sensitive and selective detection of bisphenol A (BPA) was achieved using a screen-printed carbon electrode (NFO/SPCE) modified with hydrothermally synthesized NiFe2 O4 nanoparticles. Abstract : In this study, the sensitive and selective detection of bisphenol A (BPA) was achieved using a screen-printed carbon electrode (NFO/SPCE) modified with hydrothermally synthesized NiFe2 O4 nanoparticles. The crystalline structure, surface morphology and electrical conductivity of the nanoparticles were analyzed using X-ray powder diffraction (XRD), Fourier-transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), and electrochemical impedance spectroscopy (EIS). The as-prepared NiFe2 O4 (NFO) nanoparticles exhibited a cubic crystal structure with an average crystallite size of 16 nm, as calculated using the Scherrer equation. As determined by cyclic voltammetry (CV), NFO/SPCE exhibited excellent electrochemical oxidation towards the detection of BPA. Subsequently, differential pulse voltammetry (DPV) studies revealed a rapid and stable response to the consecutive addition of BPA in a linear range of 0.02–12.5 μM with a lower limit of detection (LOD) of 6 nM, which was superior to previously reported results. In addition, the proposed method showed good stability and excellent repeatability for the determination of BPA in real samples.